Integrating Local Culture into Social Studies Curriculum: A Thai Perspective - Uthaisa, Parinrada; Sadoo, Sujittra; Tenissara, Sukanda; Theerangkuro (Pukkham), Phrapalad Weerasak; Nandapañño (Sriyort), Phramaha Supat (Journal of Buddhist Education and Research (JBER), 2023)
This paper explores the integration of local culture into the social studies curriculum from a Thai perspective. It emphasizes the importance of aligning educational content with the cultural realities of the environment to enhance students’ identity, belonging, and critical thinking skills. The study addresses the limitations of traditional curricula, which often prioritize global or Western ideas over local traditions, and argues for a curriculum that reflects Thailand’s diverse cultural background. By incorporating local customs, histories, and values, the social studies curriculum can become more relevant, engaging, and meaningful for students. This approach fosters not only academic success but also a deeper understanding of cultural identity and social responsibility. Furthermore, the paper highlights the benefits, challenges, and strategies for successfully integrating local culture into the curriculum, offering case studies of effective implementations in Thai schools. The study concludes by advocating for a balanced curriculum that promotes cultural awareness and social cohesion in Thailand.